1994
DOI: 10.1038/ng0994-15
|View full text |Cite
|
Sign up to set email alerts
|

Germline p16 mutations in familial melanoma

Abstract: The p16 gene is located in chromosome 9p21, a region that is linked to familial melanoma and homozygously deleted in many tumour cell lines. We describe eight p16 germline substitutions (one nonsense, one splice donor site and six missense) in 13/18 familial melanoma kindreds. Six of these mutations were identified in 33/36 melanoma cases in nine families, whereas two were detected in normal controls and are not disease-related. The melanoma-specific mutations were detected in 9p21-linked, but not in 1p36-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
664
3
13

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,118 publications
(692 citation statements)
references
References 17 publications
12
664
3
13
Order By: Relevance
“…In a subset of these kindreds, germline coding mutations of the CDKN2A gene (on human chromosome 9p21) co-segregate with cases of melanoma (Hussussian et al, 1994;Walker et al, 1995;Dracopoli and Fountain, 1996;FitzGerald et al, 1996; NL and DH, unpublished). The CDKN2A gene product ± designated p16 ± is a cyclin-dependent kinase (CDK) inhibitor (CDKI).…”
Section: Abstract: Familial Melanoma; Cdk6mentioning
confidence: 99%
“…In a subset of these kindreds, germline coding mutations of the CDKN2A gene (on human chromosome 9p21) co-segregate with cases of melanoma (Hussussian et al, 1994;Walker et al, 1995;Dracopoli and Fountain, 1996;FitzGerald et al, 1996; NL and DH, unpublished). The CDKN2A gene product ± designated p16 ± is a cyclin-dependent kinase (CDK) inhibitor (CDKI).…”
Section: Abstract: Familial Melanoma; Cdk6mentioning
confidence: 99%
“…When pRb is phosphorylated in these complexes the E2F proteins are free to transactivate their target genes and their products promote cell cycle progression (Sherr, 1996). Mutation of INK4a was ®rst demonstrated in familiar melanoma (Hussussian et al, 1994;Kamb et al, 1994) and INK4a remains the only member of the INK4 family shown to act as a tumor suppressor gene in humans. Mutation, deletion, or methylation of INK4a is common in many tumors, with a frequency ranging from approximately 30% in esophageal tumors, to nearly 100% in pancreatic carcinomas (Caldas et al, 1994;Ruas and Peters, 1998;Schutte et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of such an inhibitor would probably result in unregulated proliferation, thus reinforcing the support for p16 as a tumour suppressor. More recently, the availability of thepl6-/-mouse (Serrano et al, 1996) and the observation that some familial melanoma families harbour germnlne point mutations or deletions within the p16 gene (Hussussian et al, 1994;Gruis et al, 1995) have provided further evidence that p16 is a tumoursuppressor gene. A second gene in this region, p15, also behaves as a tumour suppressor (Sonada et al, 1995).…”
mentioning
confidence: 99%